The early days of Finnish game culture: Game - related discourse in Micropost and Floppy Magazine in the mid-1980s. - Nylund, Niklas; Wade, Alex (Cogent Arts & Humanities, 2016)
In the early 1980s, digital games played at home were an unprecedented cultural phenomenon. In this article, I examine the ways computer fanzines and disk magazines from the 1980s write about games and game culture, and how they contribute to the process of digital game domestication. My sources offer insight on contemporary views on multimodal games, the qualities of good games, and the different ways game making and game playing are intertwined. It is in these fanzines and disk magazines that the cultural meaning of digital games played at home is dealt with for the first time, and they provide an unique view into a complex world in which the meanings of computers, coding, games, and gaming are constantly negotiated.